THE ROLES OF LEARNING CIVIC EDUCATION IN DEVELOPING UNITY VALUES - Tri Suci Bintari Putri; Irawan Suntoro; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2012)
The aim  this research is to know and explain the roles of learning Civic Education in developing  unity values to IX Social Class students of SMA Negeri 12 Bandar Lampung years 2012/2013. This research is used descriptive quantitative method with about 153 of XI social students class as research subject. The research was taking sample about 20% or 31 students. It took questionnaire techniques as collecting data, which is having documentation and interview. The data analysis used Quadrat Chi formula. Based on data and discussion research result, it showed that part of Civic Education learning in developing unity values, mainly intransferring and application values to XI Social Class students of SMA Negeri 12 bandar Lampung years 2012/2013.Keywords : the roles of learning civic education, unity values, moral values